Economics in primary schools: an empirical experiment from Hungary - Nagy, Judit (Frontiers in Education, 2023)
The paper highlights the importance and relevance of introducing economic studies to primary schools. This research aimed to investigate the appropriate age, environment, type and composition of presentation for introducing combined economic knowledge. The 190 students participating in the research were students from three primary schools in Hungary from ten classes. Given the fact that in the case of all of the significant results, a sufficient effect size could be measured, and furthermore, the relevant test value was very high, it is unambiguously proven that the size of the sample (n=190) that was used for the examination was sufficient. The results suggest that teaching economic and financial knowledge through accounting and making lectures interactive using special tools of positive education is critical to stimulating children’s interest. Eighty per cent of the students in the study liked the combined and interactive lecture. The other goal was to investigate whether those that liked the presentation would perform better on the related knowledge test, which proved to be the In the two target groups, students in grade 3 outperformed students in grade 6 on the test. The respective education may appropriately be developed based on the close relationship between mathematics and accounting. The lectures can be adapted according to any national or international accounting standards (IFRS, etc.) and can be taught in an online classroom as well. The aim of the lectures is to develop children’s independent problem-solving skills so they can adapt the information to their own lives and financial situations. The paper fills a gap in the research by describing a successful attempt to complex economic literacy.